PERTANIAN ORGANIK SUATU ALTERNATIF PENGELOLAAN EKOSISTEM SAWAH YANG SEHAT, ALAMI DAN RAMAH LINGKUNGAN - Hadi, Mochamad; Soesilohadi, RC Hidayat; Wagiman, FX; Rahayuningsih, Yayuk (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2014)
Rice crops are the main food crops in Indonesia. In efforts to increase rice productivity , there are still many obstacles such as pest nuisance problem . In an effort to control pests for rice crop , farmers initially apply conventional farming systems are dependent applications of synthetic pesticides and synthetic fertilizers are made from chemicals . From time to time, conventional farming systems has led to environmental problems such as environmental pollution , resistance to pests and natural enemies of pests involved killing . Another strategy to reduce the negative impacts is the application of organic rice farming system as an environmentally friendly alternative . Organic farming systems is done by eliminating the use of chemicals in fertilizers , pesticides and other means of cultivation . The goal is to reduce environmental burden and environmental menciptalan rice ecosystems healthy , natural and productive. In organic rice farming system does not use synthetic chemicals in fertilizers and pesticides application . Fertilizer used is bio-fertilizers (organic) made ​​from manure, compost , and green manure . Pesticide used is a mixture of botanical pesticide made ​​from various parts of the plant that could potentially exist in the surrounding environment . The use of organic fertilizers and pesticides do not cause disturbance to the ecosystem fields because the ingredients used are organic materials that are environmentally friendly. Use other means such as the use of seed cultivation (seeds), water use and weed management done without synthetic chemicals .